2012
DOI: 10.4141/cjss2011-059
|View full text |Cite
|
Sign up to set email alerts
|

Non-growing season nitrous oxide fluxes from an agricultural soil as affected by application of liquid and composted swine manure

Abstract: Kariyapperuma, K. A., Furon, A. and Wagner-Riddle, C. 2012. Non-growing season nitrous oxide fluxes from an agricultural soil as affected by application of liquid and composted swine manure. Can. J. Soil Sci. 92: 315–327. Agricultural soils have been recognized as a significant source of anthropogenic nitrous oxide (N2O) emissions, an important greenhouse gas and contributor to stratospheric ozone destruction. Application of liquid swine manure (LSM) has been reported to increase d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 57 publications
1
13
0
3
Order By: Relevance
“…In studies with animal manures in Manitoba Asgedom et al, 2014), late fall application before freezing also did not increase N 2 O emissions. Similarly, composted and raw pig slurry applied in fall in southern Ontario did not result in fall and winter N 2 O emissions (Kariyapperuma et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…In studies with animal manures in Manitoba Asgedom et al, 2014), late fall application before freezing also did not increase N 2 O emissions. Similarly, composted and raw pig slurry applied in fall in southern Ontario did not result in fall and winter N 2 O emissions (Kariyapperuma et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…Some studies have reported on the effect of manure types and application methods, and their relationship with winter N 2 O emissions. Nitrous oxide emissions following the application of solid manure onto soils (70 kg N ha À1 ) during the non-growing season (November-April in Canada) were shown to be lower (1.0 kg N ha À1 ) than those from liquid manures (1.4 kg N ha À1 ) (Kariyapperuma et al 2012). In this case, the N 2 O emission peak occurred during the soil thawing period and Kariyapperuma et al (2012) concluded that the difference between solid and liquid manure was attributed to higher N and water contents in the liquid manure, creating more favorable conditions for N 2 O producing microbes.…”
Section: Nutrient Returns To Grazed Pastures In Winter When Animals Amentioning
confidence: 96%
“…Nitrous oxide emissions following the application of solid manure onto soils (70 kg N ha À1 ) during the non-growing season (November-April in Canada) were shown to be lower (1.0 kg N ha À1 ) than those from liquid manures (1.4 kg N ha À1 ) (Kariyapperuma et al 2012). In this case, the N 2 O emission peak occurred during the soil thawing period and Kariyapperuma et al (2012) concluded that the difference between solid and liquid manure was attributed to higher N and water contents in the liquid manure, creating more favorable conditions for N 2 O producing microbes. Regarding the application method, Ellis et al (1998) reported that when the soil temperature was <6°C, N 2 O emissions from slurry injected into soils were higher than those from mineral fertilizer or from slurry applied to the soil surface.…”
Section: Nutrient Returns To Grazed Pastures In Winter When Animals Amentioning
confidence: 96%
See 2 more Smart Citations